2012
DOI: 10.1002/wnan.1174
|View full text |Cite
|
Sign up to set email alerts
|

A systematic approach to exosome‐based translational nanomedicine

Abstract: Exosomes are a type of cell-derived extracellular nanovesicle. They relay information between cells. Some known exosome functions include immune modulation, promotion of angiogenesis, and tumor metastasis. To date, clinical use of exosomes has focused predominantly on evaluating their efficacy as cancer vaccines or diagnostically as biomarker containers. However, few investigations have explored their potential to serve as a platform for the development of semi-synthetic nanovesicles. Given their nanoscale siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
98
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 56 publications
4
98
0
Order By: Relevance
“…Multiple miRNAs associated with gastric carcinogenesis display tissue-specific expression, and can function as either tumor suppressors or oncogenes. A number of specific miRNAs are differentially expressed in gastric cancer and normal gastric mucosa: miR-21, miR-34b/c, and miR-221/222 are upregulated gastric tumors, whereas miR-124a, miR-128b, and miR-148 are downregulated (Li et al, 2012;Hood et al, 2012). A clinical study found high miR-21 levels in exosomes from ovarian carcinoma effusion supernatants by qPCR, and these were associated with poor progression-free survival times (Vaksman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple miRNAs associated with gastric carcinogenesis display tissue-specific expression, and can function as either tumor suppressors or oncogenes. A number of specific miRNAs are differentially expressed in gastric cancer and normal gastric mucosa: miR-21, miR-34b/c, and miR-221/222 are upregulated gastric tumors, whereas miR-124a, miR-128b, and miR-148 are downregulated (Li et al, 2012;Hood et al, 2012). A clinical study found high miR-21 levels in exosomes from ovarian carcinoma effusion supernatants by qPCR, and these were associated with poor progression-free survival times (Vaksman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…They relay information between tissue microenvironments [1] and can influence target cell function and differentiation [2]. They contain and protect valuable mRNA and miRNA information which corresponds to source cell normal or pathogenic processes.…”
mentioning
confidence: 99%
“…For one, exosomes naturally carry RNA, lipid, protein and metabolite cargo [1,[3][4][5] which enables their use as drug delivery vehicles. Additionally, similar to cells, exosomes contain a deformable cytoskeleton and 'gel-like' cytoplasmderived core [1]. Conceivably, these biophysical properties enhance exosome structural integrity and resistance to rupture during trafficking in vivo.…”
mentioning
confidence: 99%
See 2 more Smart Citations